Jumlah bakteri Staphylococcus aureus dan skor California Mastitis Test (CMT) pada susu kambing Peranakan Etawa akibat dipping ekstrak daun Babadotan (Ageratum conyzoides L.) - Priono, Dwi; Kusumanti, Endang; Harjanti, Dian Wahyu (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2016)
The aim of this research is to determine the effect of teat dipping of Ettawa crossbred goat using babadotan leaves (Ageratum conyzoides Linn.) extract on the number of Staphylococcus aureusin milk. The udder inflammation degree also was determined using California Mastitis Test (CMT). The treatments were post milking teat dipping using antiseptic solutions containing 1%, 3%, and 5% of babadotan leaves extract (T1, T2 and T3, respectively). Milk samples were collected at before treatment (H0) and on the day 3, 6 and 9 day of the treatments (H3, H6 and H9, respectively). Commercially antiseptic povidone iodine was used as positive control (K+). Experimental research design was completely randomized design (CRD) split plot types, with the different extract concentration as the main plot and the day of treatment as subplot. CMT scores was analyzed using Kruskal-Wallis test. The results showed that babadotan leaves extract 5% had the same effectiveness (p>0,05) with povidone iodine to reduce the number of Staphylococcus aureusin milk. All extract concentrations (1%, 3% and 5%) had the same effectiveness (H>c0,05(3)) to decrease the CMT scores by postmilking teat dip treatments for 9 days. Keywords:Teat dipping, Ageratum conyzoides (L)., Staphylococcus aureus, CMT score